Analisis Kekuatan Sambungan Las Butt joint pada Struktur Logam Baja A36 Menggunakan Simulasi SolidWorks - Septiadi Lukmawan; Adri Fato (Jurnal Teknik Mesin, 2025)
This research evaluates the mechanical strength of butt joint welds on ASTM A36 steel by comparing outcomes from laboratory testing and numerical simulations using SolidWorks. Physical experiments consisted of tensile and bending tests, while the simulation utilized the Finite Element Method (FEM). The tensile test produced an ultimate tensile strength of 498.4 MPa and a yield strength of 361.4 MPa, whereas the simulation yielded 475 MPa and 250 MPa, respectively. The bending test results indicated that the welded specimens exhibited good ductility without visible surface flaws. Differences between simulation and experimental data were mainly due to the idealized material properties in the software compared to the variability found in real specimens. These findings suggest that SolidWorks-based FEM simulation can serve as an effective preliminary tool for predicting weld joint performance, but physical testing remains necessary to validate and ensure reliability.